Monetary policy inclusive growth: empirical evidence from Philippines. / Donald Anak Sanggin - Anak Sanggin, Donald (2018)
Basically, the causality relationship between monetary policy and growth is remain uncover in context of Philippines. Mainly purposes of this study are to identify the causality relationship between monetary policy and economic growth for Philippines within years 1982-2016. Moreover, study use the time series data and most of the data is obtained from World Data bank and being analyzed by using regression analysis, assumptions test, and error test. Based on the previous study, found that the dynamic relationship between the monetary policy and growth is bidirectional, and non-directional relationship.